The year-book of facts in the Great Exhibition of 1851 : its origin and progress, construction details of the building, the most remarkable articles and objects exhibited, etc - Timbs, John, 1801-1875 (David Bogue, 1851)
Describes the origin and progress of the Great Exhibition of 1851, including the French national expositions from 1797 to 1849, the origin and construction of the Crystal Palace, the lay-out of the exhibits and the objects exhibited. There is also a description of the close of the exhibition. The appendix contains a list of the medal winners, tables of the daily number of visitors to the exhibition including the amount of money received at the doors on each day and a financial statement of the proceeds and expenditure of the exhibition. Finally a statistical note on the official catalogue is quoted from The Edinburgh review. Includes index.